Buku Cerita Bergambar sebagai Media Pembelajaran PPKN Berbasis Projek Penguatan Profil Pelajar Pancasila di MI Islamiyah Ngoro - Khumairoh, Suci; Rofi’ah, Siti (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
In an effort to enhance the effectiveness and enthusiasm in the learning process, picture story media is considered a highly effective tool in education. The use of this media enables students to learn more efficiently and enjoyably. However, at MI Islamiyah Ngoro, picture story media has never been used before. This situation has led to students feeling bored with the material focused on gotong royong (mutual cooperation) due to a lack of concrete experience, resulting in difficulties for students in expressing an authentic understanding of the value of gotong royong in daily life. This study aims to develop picture story media based on the strengthening project of the Pancasila student profile, specifically related to the values of Pancasila, particularly the value of gotong royong, using more concrete and realistic picture story media. This research employs the ADDIE model, which consists of five stages: analyzing, designing, developing, implementing, and evaluating. The study involves 27 first-grade students from MI Islamiyah Ngoro, as well as the principal and teachers. Data collection was carried out through interviews and questionnaires. The result of this development is a picture story media validated by expert validators, with a score of 98% from material experts, 90% from media experts, and 94% from instructional experts. The average score from the three validators is 94%, categorized as highly feasible. This indicates that picture story media is feasible and effective to be used in PPKN learning based on the P5 project on the topic of gotong royong.